The Effect of Fiscal Services on Taxpayer Compliance At the Sumedang Primary Tax Service Office - Fajar Hari Mulia; Tita Kartika; Fanji Farman (LPPM Universitas Sebelas April, 2020)
This study entitled The Effect of Fiscus services on Taxpayer Compliance at Sumedang Pratama Tax Office. The core problem in this study is the low level of awareness of taxpayer compliance in paying taxes. The purpose of this study is to find out how much the influence of tax authorities on tax compliance of the type of research used is quantitative descriptive method. The sampling technique uses simple random sampling method. The sample used in this study was 96 respondents from the number of samples used and can be processed. The data is then tested for quality and processed using the validity test, reliability test, and normality test after quality testing is followed by a simple regression test then the data are analyzed using the product moment correlation coefficient test, the coefficient of determination test, and the partial test (t) And the results for the tax authorities service to taxpayer compliance The coefficient of determination obtained is 0.166 or 16.6%. So it can be stated Fiscus Services has an influence of 16.6% on taxpayer compliance, while the remaining 83.4% is influenced by other factors